Assessing the Penal Harm Movement - Cullen, Francis T. (Journal of research in crime and delinquency, 1995)
This article discusses some books on penal harm. The books considered in this article are "Harm in American Penology: Offenders, Victims, and Their Communities," by Todd R. Clear, "Poor Discipline: Parole and the Social Control of the Underclass," by Jonathan Simon and "Malign Neglect: Race, Crime, and Punishment in America," by Michael Tonry. According to the author, in the aftermath of the Civil War, American corrections had devolved into a state of crisis. Prisons were filled to the brim, populated by the domestic and immigrant poor. Each historical era has its unique conversation about corrections, but these themes voiced in post-Civil War America resonate remarkably with contemporary discourse about crime and punishment. For over a decade, virtually every contemporary commentary on corrections in the U.S. has reminded us that the system is in crisis. In the 1990s, the term new penology no longer refers to a correctional philosophy that rejects vengeance in favor of offender reformation, but to an administrative style that seeks depersonalized efficiency in processing increasingly large hordes of inmates in and out of the system